Entrepreneurial orientation in high-tech and low-tech SMEs in Malopolska region - Mateusz Codogni; Joanna Duda; Rafał Kusa (Managerial Economics)
The aim of this paper is to examine the entrepreneurial orientation (EO) of SMEs in the Malopolska region of Poland. Our specific aim is to confirm the relationship between selected company characteristics (the level of technological development and stage of organizational development) and entrepreneurial orientation. A survey was conducted in a group of 95 SMEs that form hightech and low-tech industries in the Malopolska region. Our findings suggest that enterprises representing the high-tech industry exhibit higher EO than those from the low-tech industry. The findings display an imbalance in EO dimensions in both groups of enterprises, showing that innovativeness plays the most important role in enterprises from high-tech industries. The results suggest an inverse monotonic relationship between EO and a company’s age, but they do not confirm any relationship between the EO and a company’s size. Our results contribute to the theory of entrepreneurship by identifying the dependence of EO on industry type (lowtech versus high-tech) and company age.